2016
DOI: 10.3390/nu8120825
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Vitamin D Insufficiency among Nepalese Infants Despite High Prevalence of Vitamin D Insufficiency among Their Mothers

Abstract: Background: Describing vitamin D status and its predictors in various populations is important in order to target public health measures. Objectives: To describe the status and predictors of vitamin D status in healthy Nepalese mothers and infants. Methods: 500 randomly selected Nepalese mother and infant pairs were included in a cross-sectional study. Plasma 25(OH)D concentrations were measured by LC-MS/MS and multiple linear regression analyses were used to identify predictors of vitamin D status. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
2
20
1
Order By: Relevance
“… 12 , 28 Inadequate level of vitamin D is the most common reason for women with osteoporosis, and progressive deficiency of this hormone may lead to secondary hyperparathyroidism. 28 Haugen et al 29 also reported high prevalence of vitamin D insufficiency (59.8%) and deficiency (14.0%) in young women from our country. Hence, estimation of vitamin D deficiency/insufficiency becomes mandatory before reporting bone status in young as well as postmenopausal women.…”
Section: Discussionsupporting
confidence: 63%
“… 12 , 28 Inadequate level of vitamin D is the most common reason for women with osteoporosis, and progressive deficiency of this hormone may lead to secondary hyperparathyroidism. 28 Haugen et al 29 also reported high prevalence of vitamin D insufficiency (59.8%) and deficiency (14.0%) in young women from our country. Hence, estimation of vitamin D deficiency/insufficiency becomes mandatory before reporting bone status in young as well as postmenopausal women.…”
Section: Discussionsupporting
confidence: 63%
“…We did not include a healthy control group in this study, but we have data on vitamin D status in young children in the same area, both in children with less-severe pneumonia (28) and in healthy infants (31). In the study of children with lesssevere pneumonia the percentage of children with vitamin D insufficiency and deficiency was comparable to the findings in this study.…”
Section: Discussionsupporting
confidence: 50%
“…In a study conducted in Nepal vitamin D deficiency (< 20 ng/ml) was observed in 81% of the pregnant women and serum calcium level was less than the desired value in 67% of the mothers [17]. Vitamin D deficiency is observed worldwide in all age groups [13][14][15][16][17][18]. Deficiency during pregnancy and childbirth poses more threat to health than in other periods of life [4-6, 19, 20].…”
Section: Discussionmentioning
confidence: 97%
“…Few studies showed high a prevalence of vitamin D deficiency in general population [15,16]. In a study conducted in Nepal vitamin D deficiency (< 20 ng/ml) was observed in 81% of the pregnant women and serum calcium level was less than the desired value in 67% of the mothers [17]. Vitamin D deficiency is observed worldwide in all age groups [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%